POTASIUM AND MICRO FERTILIZERS APPLICATION FOR IMPROVING CASSAVA PRODUCTION HARVESTING AT 7 AND 10 MONTH AFTER PLANTING - Kukuh Setiawan (Universitas Lampung, 2020)
ABSTRACTThe harvest of cassava usually conducted by farmers in Lampung province is around 7 months after planting (MAP). Moreover, either farmers or industry cassava rarely fertilized by using potassium (KCl) and also micro fertilizers to improve the cassava production. This condition could decrease the production both root weight and strach content. Consequently, the objective of this study was to evaluate the cassava production applied by potassium and micro fertilizers harvested at 7 and 10 MAP. Treatments were arranged by factorial (2x2) in completely randomized block design with three reps used as block. First factor were First factor was two levels of KCl, 200 and 300 kg KCl/ha. Second factor was two levels of micro nutrient, 0 and 20 kg zincmicro nutrient/ha. The result showed that there was no variation of root number and root weight due to application of potassium and micro fertilizers. This means that root number and root weight were not significantly different applied by potassium and micro fertilizers. In addition, application of potassium and micro fertilizers could significantly influence shoot growth as stem dry weight and leaf dry weight at 10 MAP.Keywords: harvest, leaf dry weight, micro fetilizer, potassium, production, stem dry weight ABSTRAKCara panen ubikayu yang biasa dilakukan di tingkat petani adalah sekitar tanaman umur 7 bulan setelah tanam (BST). Selain itu, petani maupun pihak industri sangat jarang melakukan pemupukan kalium (KCl) maupun unsur mikro untuk perbaikan produksi ubikayu. Hal ini akan menyebabkan penurunan produksi baik dari bobot ubi maupun kadar pati. Oleh karena itu, tujuan penelitian ini adalah untuk mengevaluasi produksi ubikayu akibat aplikasi pemupukan kalium (KCl) dan mikro pada umur panen 7 dan 10 BST. Perlakuan disusun secara faktorial (2x2) dalam rancangan kelompok teracak lengkap (RKTL) dengan tiga ulangan sebagai kelompok. Faktor pertama adalah aplikasi dua dosis pupuk KCL, 200 dan 300 kg KCl/ha. Faktor kedua adalah aplikasi dua dosis pupuk mikro, 0 dan 20 kg Zincmikro/ha. Hasil menunjukkan bahwa tidak ada variasi pada variabel jumlah ubi dan bobot ubi akibat pemupukan kalium dan mikro. Hal ini menggambarkan bahwa aplikasi pupuk kalium dan mikro menghasilkan jumlah ubi dan bobot ubi yang tidak berbeda. Selanjutnya, aplikasi pupuk kalium dan mikro memberikan pengaruh pada variabel pertumbuhan tajuk seperti bobot kering batang dan daun pada umur 10 BST.Kata kunci: bobot kering batang, bobot kering daun, kalium, mikro, panen, produksi